2017
DOI: 10.1007/s00221-017-5015-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of variable practice on locomotor adaptation to a novel asymmetric gait

Abstract: Very little is known about the effects of specific practice on motor learning of predictive balance control during novel bipedal gait. This information could provide an insight into how the direction and magnitude of predictive errors during acquisition of a novel gait task influence transfer of balance control, as well as yield a practice protocol for the restoration of balance for those with locomotor impairments. This study examined the effect of a variable practice paradigm on transfer of a novel asymmetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
0
7
4
Order By: Relevance
“…Therefore, the data from Transfer 1 demonstrate no effect of practice group. These findings are surprising given our previous findings from this cohort, where random blocked practice had less variability in balance control compared to the other groups ( Hinkel-Lipsker and Hahn, 2017 ). It is possible that since the 1.5:1 belt asymmetry was close to that of the maximum asymmetry experienced during acquisition, all subjects were able to easily generalize their acquired pattern to this new context.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…Therefore, the data from Transfer 1 demonstrate no effect of practice group. These findings are surprising given our previous findings from this cohort, where random blocked practice had less variability in balance control compared to the other groups ( Hinkel-Lipsker and Hahn, 2017 ). It is possible that since the 1.5:1 belt asymmetry was close to that of the maximum asymmetry experienced during acquisition, all subjects were able to easily generalize their acquired pattern to this new context.…”
Section: Discussioncontrasting
confidence: 94%
“…These velocities differed according to specific practice paradigms. We observed that increased contextual interference in belt velocities on one limb led to better transfer of mediolateral balance control, but only to an extent; too much contextual interference resulted in less transfer as seen through worsened mediolateral balance control ( Hinkel-Lipsker and Hahn, 2017 ).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Practicing a motor task that is varied along some task dimension is referred to as variable practice and it is considered to be a method that enhances the ability to transfer the learned task to a novel variation of the task or to a new environment (39). This happens because, similar to the mechanism just described for the RAS technique, the continuous attempt to adjust to altered conditions creates a trial-and-error mechanism that ultimately maximizes retention (40).…”
Section: Difficulty Level Principlesmentioning
confidence: 99%